2012
DOI: 10.1109/jsen.2011.2162060
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Temperature Sensing: Review of Technology and Applications

Abstract: Abstract-Distributed temperature sensors (DTS) measure temperatures by means of optical fibers. Those optoelectronic devices provide a continuous profile of the temperature distribution along the cable. Initiated in the 1980s, DTS systems have undergone significant improvements in the technology and the application scenario over the last decades. The main measuring principles are based on detecting the back-scattering of light, e.g., detecting via Rayleigh, Raman, and Brillouin principles. The application doma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
137
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 329 publications
(152 citation statements)
references
References 44 publications
1
137
0
2
Order By: Relevance
“…However, isotropic and homogenous conditions rarely exist and spatial distribution of groundwater inflow differs strongly from lake to lake . Experimental studies highlighted a large variety of observed exchange patterns including decreasing seepage with distance from the shoreline (McBride and Pfannkuch, 1975;Brock et al, 1982;Cherkauer and Nader, 1989;Kishel and Gerla, 2002), increasing seepage with distance from the shoreline (Cherkauer and Nader, 1989;Schneider et al, 2005;Vainu et al, 2015), local hotspots of offshore seepage (Fleckenstein et al, 2009;Ono et al, 2012) and a high smallscale variability in near-shore zones (Kishel and Gerla, 2002;Blume et al, 2013;Neumann et al, 2013;Sebok et al, 2013). Most often, complex hydrogeological settings are the reason for deviations from the theoretical pattern of LGD .…”
Section: Spatial Patterns Of Lacustrine Groundwater Discharge and Thementioning
confidence: 99%
See 3 more Smart Citations
“…However, isotropic and homogenous conditions rarely exist and spatial distribution of groundwater inflow differs strongly from lake to lake . Experimental studies highlighted a large variety of observed exchange patterns including decreasing seepage with distance from the shoreline (McBride and Pfannkuch, 1975;Brock et al, 1982;Cherkauer and Nader, 1989;Kishel and Gerla, 2002), increasing seepage with distance from the shoreline (Cherkauer and Nader, 1989;Schneider et al, 2005;Vainu et al, 2015), local hotspots of offshore seepage (Fleckenstein et al, 2009;Ono et al, 2012) and a high smallscale variability in near-shore zones (Kishel and Gerla, 2002;Blume et al, 2013;Neumann et al, 2013;Sebok et al, 2013). Most often, complex hydrogeological settings are the reason for deviations from the theoretical pattern of LGD .…”
Section: Spatial Patterns Of Lacustrine Groundwater Discharge and Thementioning
confidence: 99%
“…So far, there is no clear picture about the role of lake sediment characteristics in controlling LGD patterns and observations seem to be very site specific. For example, Kidmose et al (2013) found that low permeable lacustrine sediments can completely prevent groundwater upwelling, whereas Vainu et al (2015) observed LGD through low permeable lacustrine sediments. Kishel and Gerla (2002) associated small-scale variabilities in LGD with small-scale heterogeneities in hydraulic conductivities (Kishel and Gerla, 2002); Schneider et al (2005) found no correlation between seepage rates and sediment characteristics.…”
Section: Spatial Patterns Of Lacustrine Groundwater Discharge and Thementioning
confidence: 99%
See 2 more Smart Citations
“…A distributed temperature sensor (DTS) can span large flow fields and function in environments that are unsuitable for image-based techniques 8 . There are also DTSs based on Raman and Brillouin scattering 9,10 , but sensors based on Rayleigh scattering and SWI provide spatial and temporal resolution more suitable for typical fluid dynamics experiments.…”
Section: Introductionmentioning
confidence: 99%